2023
DOI: 10.7759/cureus.34426
|View full text |Cite
|
Sign up to set email alerts
|

Re-Tear Rates Following Rotator Cuff Repair Surgery

Abstract: Re-tears following rotator cuff repair surgery are a common occurrence. Previous studies have identified several factors that have been shown to increase the risk of re-tears. The purpose of this study was to evaluate the rate of re-tear following primary rotator cuff repair and to identify the factors that may contribute to this rate. MethodThe authors performed a retrospective review, looking at rotator cuff repair surgeries performed between May 2017 and July 2019 performed in a hospital by three specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Although age-related tendon degeneration and tears also/frequently occurred in men, one study including men and women aged 45-89 years revealed that female gender is a risk factor for massive RC tears [39]. Additionally, a recent study investigating RC re-tear rates in men and women aged 33 to 79 years has shown that re-tear rates after RC repair were more common in women-possibly related to the regional BMD decline in women after menopause, [40,41]. These data appear to be in line with our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Although age-related tendon degeneration and tears also/frequently occurred in men, one study including men and women aged 45-89 years revealed that female gender is a risk factor for massive RC tears [39]. Additionally, a recent study investigating RC re-tear rates in men and women aged 33 to 79 years has shown that re-tear rates after RC repair were more common in women-possibly related to the regional BMD decline in women after menopause, [40,41]. These data appear to be in line with our study results.…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely owing to the radiological outcomes being examined 6 months after surgery, resulting in incomplete data being considered. According to the literature, most retears occur within 6 months after surgery [29][30][31]; nevertheless, follow-up within 6 months is considered too early to evaluate the continuity of the healed rotator cuf tear. It is worth noting that the study by Park et al [10] was a signiicant source of subgroup heterogeneity for two reasons: irst, the evidence for this study was a case series with a low level of evidence relative to other studies; second, the study only reported the This meta-analysis also revealed that delamination results in lower complete healing rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, postoperative complications can significantly impact the effectiveness of the treatment for this condition. Rotator cuff retear is a prominent post-arthroscopic rotator cuff repair (ARCR) complication, with a significant risk of retear ranging from 8.3% to 27.3% (Fu et al, 2020 ; Davey et al, 2023 ; Routledge et al, 2023 ; Tsuchiya et al, 2023 ). Tear recurrence can be influenced by factors including: (1) inadequate strength of the initial repair construct, and (2) inappropriate postoperative rehabilitation causing structural failure of the repair (Bigliani et al, 1992 ; Neviaser and Neviaser, 1992 ; Boileau et al, 2005 ; Cho et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%